Study on the Characteristics and Prevention Strategies of Injury Accidents of Chinese Young Athletes- Statistical Analysis Based on 68 Civil Judgment Documents - Ya Wen Guo, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to analyze the current situation of juvenile athletes' injury accident judgment documents, so as to provide reference for sports related personnel and judicial personnel. In this paper, 68 judgment documents of injury accidents of young athletes in courts at all levels in China from May 20, 2014 to December 23, 2020 were collected, and the judgment results of injury accidents of young athletes were analyzed by content analysis method. The results show that: the injury age stage, the time of the accident, the type of injury, the injured part, the degree of disability, the type of defendant and the liability of compensation of young athletes have seven characteristics. And based on the characteristics of young athletes' injury accidents, five prevention strategies are proposed to continue to deepen the integration of sports and education, fully equip school sports facilities, strengthen the teaching and training of P.E. teachers, strengthen the safety of youth sports, and popularize school sports liability insurance.